The Counselor's Role in Helping Students Discover their Learning Styles - Yulianti Yulianti; Erna Rahmawati Hatijah; Eliza Putriansyah; Angga Widiyansyah Pratama (Universitas Muhammadiyah Enrekang, 2023)
Learning styles are simple methods for assimilating, managing, storing and applying information. Teachers can improve students' academic performance by understanding their individual learning styles and helping them learn according to the learning styles that are most effective for them. This recognizes that each student has a unique learning type/style, and the use of appropriate learning styles can facilitate learning, information processing, and communication in the classroom. Therefore, students should not limit themselves to just one learning style, but rather combine different approaches according to their needs. For this reason, the role of counselors is very important in helping students find their learning style.